1993
DOI: 10.3168/jds.s0022-0302(93)77440-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Increasing Ruminal Butyrate on Milk Yield and Blood Constituents in Dairy Cows Fed a Grass Silage-Based Diet

Abstract: The effects of increased ruminal supply of butyrate on milk yield, milk composition, and blood metabolites were studied in four lactating cows in a 4 x 4 Latin square design. The basal diet comprised grass silage, hay, and concentrate (34:22:42, DM basis) and was supplemented with isoenergetic VFA infusions (3.58 Mcal/d). A 3:1 molar mixture of acetate and propionate was replaced gradually with butyrate at the rates of 0, 200, 400, or 600 g/d. When the amount of infused butyrate increased, isobutyrate, butyrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
65
3

Year Published

1997
1997
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 17 publications
17
65
3
Order By: Relevance
“…All data points are presented as means within a study. butyrate, Huhtanen et al (1993) found increasing milk production, however, these authors infused butyrate continuously into the rumen and the cows did not experience the dramatic diurnal changes in peripheral butyrate concentration as in the present study.…”
Section: Hourcontrasting
confidence: 55%
“…All data points are presented as means within a study. butyrate, Huhtanen et al (1993) found increasing milk production, however, these authors infused butyrate continuously into the rumen and the cows did not experience the dramatic diurnal changes in peripheral butyrate concentration as in the present study.…”
Section: Hourcontrasting
confidence: 55%
“…It may be speculated that part of the energy from the concentrates was used to maintain the cows and for gaining weight, since the cows did gain weight. It has been established that the efficiency of energy utilization for milk production depends on the ratio of molar proportions of VFAs in the rumen (Huhtanen et al, 1993). A mean propionic to acetic acid ratio of 15:64 was found to prevail in the rumen of the cows in the study for all the diets.…”
Section: Milk Productionmentioning
confidence: 99%
“…Extracellular ketone bodies are represented in eqn (40) because de novo milk fat synthesis is positively correlated with -hydroxybutyrate concentrations in blood (Huhtanen et al, 1993). It is not clear whether the e!ect is mediated through the conversion of -hydroxybutyrate to butyrate, which then serves as a substrate primer for the initiation of chain-elongation, or via some other mechanism.…”
Section: Milk Fatmentioning
confidence: 99%